Robust Design of Multilayer Optical Coatings by Means of Evolution Strategies - Bäck, Thomas; Hammel, Ulrich; Wiesmann, Dirk (Universität Dortmund, 1998)
Robustness is an important requirement for almost all kinds of products. In this article we show how evolutionary algorithms can be applied for robust design based on the approach of Taguchi. As an example we consider the design of multilayer optical coatings most frequently used for optical filters.
Reihe Computational Intelligence ; 25
Keywords: 004